'I'm my own boss…': Active intermediation and 'entrepreneurial' worker agency in the Australian gig-economy. (November 2020) - Barratt, Tom; Goods, Caleb; Veen, Alex
Platform firm in the gig-economy are disrupting work as a social practice, production systems and recasting capital-labour relations. This qualitative study examines worker agency in the Australian food-delivery sector; a segment where platforms actively intermediate both product and labour markets. Within this sector, worker agency poses a potential challenge to platform-organisations; however this study reveals how these platforms' work organisation and market regulation constrain agency potential. Shaped by the work's spatio-temporal features, organisational fixes and institutional context, it is shown how food-delivery workers, transiently attached to the labour market, predominantly engage in 'entrepreneurial agency' – a low-level agency expression aimed at materially improving individual conditions and aligning with, rather than challenging, platforms' business models.